2022
DOI: 10.3390/microorganisms10050857
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Vaccine Alpha and Delta Variant Breakthrough Infections Are Rare and Mild but Can Happen Relatively Early after Vaccination

Abstract: (1) Background: Some COVID-19 vaccine recipients show breakthrough infection. It remains unknown, which factors contribute to risks and severe outcomes. Our aim was to identify risk factors for SCoV2 breakthrough infections in fully vaccinated individuals. (2) Methods: We conducted a retrospective case-control study from 28 December 2020 to 25 October 2021. Data of all patients with breakthrough infection was compared to data of all vaccine recipients in the Canton of Basel-City, Switzerland. Further, breakthr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…These features of mRNA vaccines raised high hopes for the worldwide SARS-CoV-2 vaccination campaign to curb the ongoing pandemic. Unfortunately, however, the virus mutated more rapidly and new variants emerged that would overcome vaccine-induced immunity (9)(10)(11)(12). The wild-type virus was consecutively succeeded by the alpha, delta, and omicron variants accumulating mutations in the spike protein (13).…”
Section: Introductionmentioning
confidence: 99%
“…These features of mRNA vaccines raised high hopes for the worldwide SARS-CoV-2 vaccination campaign to curb the ongoing pandemic. Unfortunately, however, the virus mutated more rapidly and new variants emerged that would overcome vaccine-induced immunity (9)(10)(11)(12). The wild-type virus was consecutively succeeded by the alpha, delta, and omicron variants accumulating mutations in the spike protein (13).…”
Section: Introductionmentioning
confidence: 99%
“…The first approved vaccines were based on the novel mRNA technology and triggered a robust immune response resulting in high protection efficiency [4][5][6][7] . This was reflected in the low frequency of breakthrough infections among the vaccinated, which were mostly caused by the alpha variant (Pango lineage B.1.1.7), and resulted in mild disease 8,9 . However, similar to infection-induced immunity, the immune response to SARS-CoV-2 vaccines rapidly declines below the level required for protection from infection 10,11 .…”
mentioning
confidence: 99%
“…In our study, about 29% of the participants had a history of COVID-19 infection, yet the breakthrough infection rates were high. A survey of 126,586 vaccine recipients reported that working in healthcare centers is associated with a higher risk of breakthrough infection ( 40 ). Although exposure is essential, our study’s rate of 5.13% breakthrough cases is very high compared to previous studies on healthcare workers ( 33 , 40 ).…”
Section: Discussionmentioning
confidence: 99%